LlKASI TEORI PILIHAN BIDANG VOKASI PADA PEMANTAPAN KARIER SISWA PENDIDlKAN KEJURUAN - Th. Sukardi (LPMPP Universitas Negeri Yogyakarta, 2006)
Among the main concerns in running business companies are job description, positioning, and design, ehose planning requires through and detailed analysis. how detailed the analysis is depends on the theories adopted for reference. the theories commonly employed in determining vocational options can also be used as references in providing employees or prospective employees with information of job description, positioning, and design.